2018
DOI: 10.3389/fpsyg.2018.02376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Aerobic Spin Intervention on Resting State Networks in Previously Sedentary Older Adults

Abstract: Objective: We have previously demonstrated that aerobic exercise improves upper extremity motor function concurrent with changes in motor cortical activity using task-based functional magnetic resonance imaging (fMRI). However, it is currently unknown how a 12-week aerobic exercise intervention affects resting-state functional connectivity (rsFC) in motor networks. Previous work has shown that over a 6-month or 1-year exercise intervention, older individuals show increased resting state connectivity of the def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 59 publications
0
37
1
Order By: Relevance
“…Mean trial duration was 5.25 months (SD = 3.03), with the longest trial lasting 12 months and the shortest just six weeks. Intervention conditions primarily consisted of a combination of supervised and unsupervised walking sessions titrated so that participants reached 50-80% of their maximum heart rate, though several interventions also included other aerobic activities in their exercise protocols, such as cycling (McGregor et al, 2018;Prehn et al, 2017), dancing (Voss et al, 2019), and/or jogging (Flodin, Jonasson, Riklund, Nyberg, & Boraxbekk, 2017). One study employed a commercially available video game designed to enhance fitness that included a variety of both aerobic (dancing, running in place) and strength (e.g., yoga) exercises, with participants completing all exercise sessions independently in their own homes.…”
Section: Effect Of Exercise Interventions On Functional Network Organmentioning
confidence: 99%
See 3 more Smart Citations
“…Mean trial duration was 5.25 months (SD = 3.03), with the longest trial lasting 12 months and the shortest just six weeks. Intervention conditions primarily consisted of a combination of supervised and unsupervised walking sessions titrated so that participants reached 50-80% of their maximum heart rate, though several interventions also included other aerobic activities in their exercise protocols, such as cycling (McGregor et al, 2018;Prehn et al, 2017), dancing (Voss et al, 2019), and/or jogging (Flodin, Jonasson, Riklund, Nyberg, & Boraxbekk, 2017). One study employed a commercially available video game designed to enhance fitness that included a variety of both aerobic (dancing, running in place) and strength (e.g., yoga) exercises, with participants completing all exercise sessions independently in their own homes.…”
Section: Effect Of Exercise Interventions On Functional Network Organmentioning
confidence: 99%
“…It is possible that non-aerobic exercise exerts unique effects on DMN connectivity compared to aerobic exercise. Indeed, there is evidence that improvements in aerobic fitness levels may mediate some proportion of the effects of exercise on DMN connectivity (Flodin et al, 2017;McGregor et al, 2018), indicating that aerobic exercise may contribute more robustly to functional network integrity compared to other nonaerobic forms of exercise. Further, one study found evidence to suggest that the magnitude and direction of the relationship between exercise and DMN connectivity is dependent on premorbid cognitive status (Chirles et al, 2017).…”
Section: Effect Of Exercise Interventions On Functional Network Organmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the previous rs-fMRI literature was, however, not focused on investigating the transient effects of acute exercise bouts, but rather on long-term effects of repeated exercise training over several months [1][2][3][4]: Stronger rs-FC was reported between the right parahippocampal gyrus and motor, sensory, and mood regulating areas after 16 weeks of training [4]. On the other hand, 12 weeks of exercise induced increased FC between the default mode network (DMN) and primary motor areas [3], eventually indicating improved motor performance. Conversely, another study found no significant changes in intrinsic brain activity after a six months of aerobic exercise [2].…”
Section: Introductionmentioning
confidence: 99%